Red cell distribution width (RDW) is correlated to time of oxygen desaturation < 90% and length of sleep apneas in patients with sleep disorder breathing (SDB) and acute heart failure with preserved ejection fraction (HFpEF) - Stamerra, Cosimo A.; D'Elia, Emilia; Gori, Mauro; Roncali, Federica; Cereda, Alberto; Gavazzi, Antonello; Ferri, Claudio; Senni, Michele (Frontiers in Cardiovascular Medicine, 2023)
Background Heart failure with preserved ejection fraction (HFpEF) is very frequently associated to sleep breathing disorders (SDB). Red blood cell distribution width (RDW) has been shown to be a potential inflammatory index linked to the degree of hypoxia and oxidative stress. Aim To identify the existence of a possible relationship between sleep apnea, oxygen saturation (SaO2) and RDW in a population of subjects affected by acute HFpEF (AHFpEF). Methods AHFpEF patients with known history of SDB were enrolled and performed blood chemistry, echocardiography, and 24-h polysomnography (PSG). Results A total of 34 acute HFpEF patients (mean age 72.8 +/−8.63) were enrolled in the study. A control group of 24 non-HF patients were considered. Compared to controls, HFpEF patients showed a higher mean apnea hypopnea index (AHI), with prevalence of central apneas. A moderate to severe desaturation pattern was observed in AHFpEF vs. controls. RDW was significantly higher in AHFpEF patients vs. controls (mean value 14.7 +/−2.6 % vs. 9.1 +/−2.2, p < 0.05). In AHFpEF, RDW showed a positive correlation with time of SaO2 < 90% (r = 0.35, p = 0.04), and with mean length of apneic events (60 +/−28 s, r = 0.29, p = 0.03). Conclusion In patients with AHFpEF and SDB, a dependence relationship between RDW and duration of oxygen desaturation was observed, as if oxidative stress and inflammation related to RDW increase could also be linked to severity of sleep disorders in this population.